Improving Teachers' Pedagogical Competence in Developing Project Modules in the Implementation of the Independent Curriculum at MTsN 1 Baubau - Nurul Hafidzah Asra; Yaya Suryana (al-Afkar, Journal For Islamic Studies, 2025)
Increasing teacher competence in developing project modules on the independent curriculum at MTsN 1 Baubau resulted in a module design that took the theme of local wisdom with the sub-theme "Antolona tala haroa in the celebration of Kandea-kandea". The selection of this sub-theme as a form of students is guided to practice the identity and cultural diversity of the nation that is realistic so that its application and understanding are in accordance with the local socio-cultural culture. The stages of project implementation start from the teacher designing modules, presenting teaching materials introducing the concept of Wolio cultural culture, presenting examples of making cakes and regional specialties, providing basic understanding tests, facilitating students to be able to discuss and collaborate, directing students to carry out work degrees, and conducting formative, summative assessments and learning reflections.